Diversifikasi Pengolahan Ikan Lele dengan Konsep Zero Waste (Nugget dan Kerupuk) - Siti Fatimatul Munawaroh; Agoes M. Jacoeb (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Catfish farming conducted in Karanggatak Village, Klego District, Boyolali Regency is an effort to earn income during the dry season and dry land. This catfish cultivation business is a program carried out by the local village government and will later be developed into a catfish village. This program aims to utilize catfish with the concept of zero waste to increase higher economic results in order to create added value for catfish. Added value is expected to help improve the economy during the dry season. Diversification of catfish processing aims to provide training to the community to process catfish into nuggets and chips that produce no leftovers. The concept of zero waste is used because this concept can provide more effective results for utilizing catfish and obtain greater profits. The method used is lectures, discussions, and demonstrations. The results obtained are increased skills and additional knowledge to process catfish, so they can support the village catfish program. Keywords: catfish, chips, nugget, zero waste